Sacralization of lumbar vertebrae-prevalence and association with low back ache and radiculopathy - Shreyas, N.; Shetty, Sanath Kumar; Mahalingam; Sherlekar, Vinay V. (International Journal of Research in Orthopaedics, 2024)
Background: Low back pain (LBP) is a prevalent condition, often associated with various anatomical anomalies, including lumbar sacralization, that is, the fusion of the fifth lumbar vertebra (L5) with the sacrum. This study aims to evaluate the prevalence of sacralization among LBP patients and its relationship with radiculopathy. Methods: A retrospective study was conducted at the department of orthopaedics, Justice KS Hegde charitable hospital, from January 1, 2023, to July 31, 2024. Patients aged 18-75 years presenting with LBP who underwent lumbosacral radiographs were included. Demographic and clinical data were collected, and sacralization types were classified using the Castellvi system. Statistical analyses were performed using the chi-square test. Results: Among 771 radiographs analysed, the prevalence of sacralization was 10.1%. Most subjects were over 41 years old (81.6%), with a majority being female (54.5%). Type I A was the most common form of sacralization (30.77%). A significant association between sacralization and radiculopathy was observed, with 70 of the 78 subjects with sacralization experiencing radiculopathy (p<0.0005). Conclusions: This study indicates a noteworthy association between sacralization and radiculopathy in patients with LBP. Given the low prevalence of sacralization, the findings emphasize the importance of recognizing anatomical variations in clinical evaluations of patients with low back ache, particularly in older populations. Further research is warranted to explore the implications of these anatomical anomalies on treatment strategies and patient outcomes.